Multilayered mechanism of CD4 downregulation by HIV-1 Vpu involving distinct ER retention and ERAD targeting steps. - Javier G Magadán; F Javier Pérez-Victoria; Rachid Sougrat; Yihong Ye; Klaus Strebel; Juan S Bonifacino (PLoS Pathogens, 2010)
A key function of the Vpu protein of HIV-1 is the targeting of newly-synthesized CD4 for proteasomal degradation. This function has been proposed to occur by a mechanism that is fundamentally distinct from the cellular ER-associated degradation (ERAD) pathway. However, using a combination of genetic, biochemical and morphological methodologies, we find that CD4 degradation induced by Vpu is dependent on a key component of the ERAD machinery, the VCP-UFD1L-NPL4 complex, as well as on SCF(beta-TrCP)-dependent ubiquitination of the CD4 cytosolic tail on lysine and serine/threonine residues. When degradation of CD4 is blocked by either inactivation of the VCP-UFD1L-NPL4 complex or prevention of CD4 ubiquitination, Vpu still retains the bulk of CD4 in the ER mainly through transmembrane domain interactions. Addition of a strong ER export signal from the VSV-G protein overrides this retention. Thus, Vpu exerts two distinct activities in the process of downregulating CD4: ER retention followed by targeting to late stages of ERAD. The multiple levels at which Vpu engages these cellular quality control mechanisms underscore the importance of ensuring profound suppression of CD4 to the life cycle of HIV-1.